Sami law and rights in Norway – with a focus on recent developments - Ravna, Øyvind (Taylor & Francis, 2020)
This is an Accepted Manuscript of a book chapter published by Routledge/CRC Press in Routledge Handbook of Indigenous Peoples in the Arctic on 04. december 2020, available online: https://www.routledge.com/Routledge-Handbook-of-Indigenous-Peoples-in-the-Arctic/Koivurova-Broderstad-Cambou-Dorough-Stammler/p/book/9780367220396. This chapter addresses the legal protection of the Sámi as Indigenous peoples in Norway and thus the laws that protect Sámi language, culture and way of life or, in other words, Sámi law. The chapter describes the development of Sámi law and Sámi legal protections over the past 30 years, with a primary focus on recent developments and current legal status. Through this review, the chapter summarises the latest advances in international law related to the Sámi, the process of surveying and recognising land rights in Finnmark (the most central Sámi area in Norway) and the latest amendments to the Reindeer Husbandry Act. Questions about the right to the usage, management and control of natural resources, or “land and water”, in the Sámi area of Norway therefore occupy a central place in this examination.